An Alaska anthology : interpreting the past - Haycox, Stephen W.; Mangusso, Mary Childers (University of Washington Press, 1996)
In An Alaska Anthology, twenty-five contemporary scholars explore the region's pivotal events, significant themes, and major agents, Native, Russian, Canadian, and American. The essays chosen for this anthology represent the best writing on Alaska, giving great depth to our understanding and appreciation of its history from the days of Russian-American Company domination to the more recent threat of nuclear testing by the Atomic Energy Commission and the influence of oil money on inexperienced politicians. Readers may be familiar with an earlier anthology, Interpreting Alaska's History, from which the present volume evolved to accommodate an explosion of research in the previous decade. While a number of the original pieces were found to be irreplaceable, more than half of the essays are new. The result is a fresh perspective on the subject and an invaluable resource for students, teachers, and scholars.